Material regulation and control method for preparing rock wool and mineral wool from dechlorinated waste incineration fly ash

By conducting component analysis and adjustment of component ratio of waste incineration fly ash, the problems of high cost of fly ash disposal and low degree of resource utilization are solved, and the efficient resource utilization and environmental friendliness of fly ash are achieved.

CN119551909APending Publication Date: 2025-03-04EVERBRIGHT ENVIRONMENTAL TECH CHINA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411651289.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art has problems such as unfriendly environment, low resource degree and high disposal cost when dealing with waste incineration fly ash, and the added value of fly ash molten glass products is low, making it difficult to widely use.

Method used

The components of dechlorinated fly ash were analyzed by X-ray fluorescence analysis, and the ratio of (SiO2+Al2O3)/(CaO+MgO) and Al2O3/MgO was adjusted to classify and convert components between 1.1-2.2 and 1.5-2.2, and reasonably adjust the mass proportion of the main components of dechlorinated fly ash to ensure that its viscosity at 1400°C is less than 3Pa·s and the melting temperature is less than 1450°C.

Benefits of technology

The material regulation of dechlorinated fly ash is realized, so that the viscosity-temperature performance of its melt meets the requirements of industrial fiber formation, reduces the cost of fly ash disposal, increases the degree of resource utilization, and reduces environmental risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551909A_ABST
    Figure CN119551909A_ABST
Patent Text Reader

Abstract

The invention discloses a material regulation and control method for preparing rock wool and mineral wool from dechlorinated waste incineration fly ash, which is characterized in that the mass ratio of main components of the dechlorinated waste incineration fly ash is regulated and optimized by using an additive, so that the viscosity-temperature performance of a dechlorinated fly ash melt meets the process requirements of industrial fiber forming. According to the invention, classification is carried out according to the influence of each oxide on the viscosity-temperature performance of the slag and the performance of the mineral wool fiber, and a forming body, an intermediate and a modifier of a mineral wool glass fiber network, which are similar to SiO2, Al2O3 and CaO in properties, are divided into corresponding SiO2, Al2O3 and CaO components after conversion according to corresponding conversion coefficients; the viscosity of the adjusted ash sample at 1400 DEG C is less than 3 Pas, the melting temperature is less than 1450 DEG C, the fiber forming temperature interval corresponding to the viscosity of 1-3 Pas is greater than 100 DEG C, the viscosity-temperature change gradient is small, and the operation of a fiber forming process is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hazardous waste disposal, and specifically relates to a material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash. Background Art

[0002] With the increase of domestic waste incineration disposal capacity, the amount of fly ash generated by the incineration of domestic waste has also increased year by year. Since fly ash contains heavy metals such as Zn, Pb, Cu, Cr, Cd, Ni, as well as toxic and harmful substances such as soluble salts, dioxins and furans, it is listed as HW18 hazardous waste in the "National List of Hazardous Wastes". The fly ash disposal technologies that have been widely used at present mainly include solidification-stabilization landfill and cement kiln co-disposal. Landfill occupies a large amount of land resources, and there are problems such as non-compliance and prominent environmental hazards; cement kiln co-disposal is limited by the operation of cement kilns, the distribution of cement kiln resources, and most of the heavy metals remain in cement, and there is still a problem of waste disposal after the end of the product life. Therefore, it is urgent to develop new fly ash treatment technologies that are environmentally friendly and highly resource-based.

[0003] In order to improve the resource utilization of fly ash, water washing and dechlorination are currently mostly used to recover the chloride salts in fly ash, and then coordinated with high-temperature melting, low-temperature pyrolysis, geopolymerization and solidification and other disposal technologies. Among them, fly ash water washing and melting vitrification is the most thorough fly ash disposal technology with the least environmental risk, but there are problems such as high melting energy consumption and low added value of glass products, which makes the operating cost high and not widely used. If the glassy slag of fly ash melting is used to prepare high-value products, it can greatly offset the cost of fly ash melting.

[0004] Rock wool and slag wool are the main thermal insulation materials, widely used in construction, industry, shipbuilding, agriculture and other fields, with large consumption and high product added value. Fly ash contains the main components such as CaO, SiO2, Al2O3, MgO required for the production of rock wool and slag wool, and can be used as raw materials for the production of rock wool and slag wool. However, the main components of the rock wool and slag wool melt have an important influence on the viscosity-temperature properties and crystallization properties of the melt, and determine whether the melt can meet the requirements of the cotton making process. Therefore, a method for regulating the components of rock wool and slag wool prepared by melting fly ash is developed to help the high-value resource utilization of fly ash, thereby reducing the cost of fly ash disposal, which is of significant significance to the resource utilization of fly ash and the promotion of the waste incineration industry. Summary of the invention

[0005] Technical problems solved: In response to the above technical problems, the present invention provides a material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash, which can effectively solve the shortcomings of the above method in disposing fly ash, such as being unfriendly to the environment, having a low degree of resource utilization, and having a high cost for fly ash disposal.

[0006] Technical solution: A material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash, comprising the following steps:

[0007] S1. X-ray fluorescence analysis was used to analyze the dechlorinated fly ash composition and obtain the SiO 2 、Al 2 O 3 , CaO, MgO, Fe 2 O 3 ,FeO,Na 2 O.K 2 O and TiO 2 The mass percentage of each component is normalized;

[0008] S2, adjust the dechlorinated fly ash (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio, so that (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio is 1.1-2.2; adjust the Al content in dechlorinated fly ash 2 O 3 / MgO ratio, so that Al 2 O 3 / MgO ratio is 1.5-2.2 to obtain a mixed material;

[0009] S3, classify the oxides in the adjusted mixture according to their effects on the slag properties and mineral wool fiber properties, and divide them into SiO 2 、Al 2 O 3 , CaO, and the like, and are converted into the corresponding SiO 2 、Al 2 O 3 , CaO components, the conversion method is as follows:

[0010] SiO 2 * =SiO 2

[0011] Al 2 O 3 * =Al 2 O 3 +102 / 160·Fe 2 O 3 +102 / 79.8 TiO 2

[0012] CaO * =CaO+56 / 40·MgO+56 / 46·Na 2 O+56 / 94·K 2 O+56 / 72·FeO

[0013] The obtained SiO 2 * 、Al 2 O 3 * 、CaO * Perform normalization processing;

[0014] S4. Determine the rationality of the materials for the thermal insulation cotton made of dechlorinated fly ash after adjustment to ensure (SiO 2 *+Al 2 O 3 *) / CaO* ratio is 1-1.7, SiO 2 * / Al 2 O 3 *The ratio is 2-7. If this condition is not met, the dechlorinated fly ash components need to be readjusted until the condition is met;

[0015] S5. After adjusting the mass proportion of the main components in the dechlorinated fly ash, the composition of the dechlorinated fly ash meets the material requirements for preparing thermal insulation cotton, and the key properties of the high-temperature melt after melting meet the following requirements: the viscosity of the slag at 1400°C is less than 3Pa·s, and the melting temperature of the slag is less than 1450°C.

[0016] Preferably, the method for adjusting the mass percentage of the dechlorinated fly ash component in step S2 is:

[0017] If (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio is less than 1.1, then adding SiO-rich 2 、Al 2 O 3 Ore or solid waste additives;

[0018] If (SiO 2 +Al 2 O 3 If the ratio of ) / (CaO+MgO) is greater than 2.2, ore or solid waste additives rich in CaO and MgO are added to the dechlorinated fly ash;

[0019] If 1.1≤(SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio ≤2.2, and Al 2 O 3 / MgO ratio <1.5, then add kaolinite to the dechlorinated fly ash to carry out Al 2 O 3 Adjustment of quality scores;

[0020] If 1.1≤(SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio ≤2.2, and Al 2 O 3 If the ratio of MgO to MgO is greater than 2.2, magnesite is added to the dechlorinated fly ash to adjust the MgO mass fraction.

[0021] If 1.1≤(SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio ≤ 2.2, and 1.5 ≤ Al 2 O 3 / MgO ratio ≤2.2, the first stage adjustment is completed.

[0022] Furthermore, SiO-rich 2 、Al 2 O 3 The ore or solid waste additives are one or more of quartz sand, kaolinite, fly ash, and iron tailings; the ore or solid waste additives rich in CaO and MgO are one or more of limestone, dolomite, magnesite, blast furnace slag, and steel slag.

[0023] Furthermore, in the composition adjustment, when (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio ≥1.5, then adjust the Fe content in the dechlorinated fly ash. 2 O 3 + FeO mass fraction>4%, adjustment method is:

[0024] When (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio ≥1.5, and Fe 2 O 3 When the mass fraction of +FeO is less than 4%, Fe-rich 2 O 3 , FeO ore or solid waste additives;

[0025] When 1.1≤(SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio ≤1.5 or 1.5<(SiO2 +Al 2 O 3 ) / (CaO+MgO) ratio ≤2.2 and Fe 2 O 3 When the mass fraction of +FeO is ≥4%, the second stage adjustment is completed.

[0026] Furthermore, Fe-rich 2 O 3 , FeO ore or solid waste additives are one or more of hematite, Bayer red mud, and iron oxide scale.

[0027] Preferably, the specific method for readjusting the dechlorinated fly ash components in step S4 is:

[0028] If (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio is less than 1, and the SiO content needs to be appropriately increased. 2 、Al 2 O 3 The amount of ore or solid waste additives used;

[0029] If (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio is greater than 1.7, and the amount of ore or solid waste additives containing CaO and MgO needs to be appropriately increased;

[0030] If 1≤(SiO 2 * +Al 2 O 3 * ) / CaO * The ratio is ≤1.7, and SiO 2 * / Al 2 O 3 * The ratio is less than 2 or greater than 7, and the SiO 2 、Al 2 O 3 The proportion of ore or solid waste additives used to carry out SiO 2 and Al 2 O 3 Adjustment of the proportion;

[0031] If 1≤(SiO 2 * +Al2 O 3 * ) / CaO * The ratio is ≤1.7, and 2≤SiO 2 * / Al 2 O 3 * If the ratio is ≤7, the adjustment is completed.

[0032] Preferably, the viscosity η at 1400° C. in step S5 is calculated as follows:

[0033]

[0034] The calculation formula of the melting temperature of slag is:

[0035] T=-742.705X 3 +3683.7511X 2 -5753.5189X+4219.9091

[0036] Where X=(SiO 2 * +Al 2 O 3 * ) / CaO *

[0037] The fiber-forming temperature range corresponding to the slag viscosity of 1-3 Pa·s is greater than 100°C.

[0038] Beneficial effects: The present invention provides a material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash, and uses additives to adjust and optimize the mass proportion of the main components of dechlorinated waste incineration fly ash, so that the viscosity-temperature performance of the dechlorinated fly ash melt meets the process requirements of industrial fiber formation. The present invention classifies the effects of various oxides on the viscosity-temperature performance of slag and the performance of mineral wool fibers into 2 、Al 2 O 3 , CaO, and the like, and are converted into the corresponding SiO 2 、Al 2 O 3 , CaO components; then based on the multivariate phase diagram and viscosity-temperature diagram, the adjustment of the mass proportion of each component of the dechlorinated fly ash is guided, which has a wide range of raw material adaptability and is easy to implement; the adjusted ash sample has a viscosity of less than 3Pa·s at 1400℃, a melting point of less than 1450℃, and a fiberizing temperature range corresponding to the viscosity of 1-3Pa·s is greater than 100℃, the viscosity-temperature gradient is small, and the fiberizing process is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 It is a flow chart of the control method of the present invention. DETAILED DESCRIPTION

[0040] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments:

[0041] Example 1

[0042] The material control method for preparing rock wool and slag wool using dechlorinated fly ash from Plant A is as follows: Figure 1 As shown, the following steps are included:

[0043] Step 1: Analyze the components of dechlorinated fly ash using X-ray fluorescence analysis and chemical titration:

[0044] The mass percentage of the main components of dechlorinated fly ash is: SiO 2 -8.05%, Al 2 O 3 -5.90%, CaO-43.07%, MgO-5.11%, Fe 2 O 3 -2.13%, FeO-1.31%, Na 2 O-0.75%, K 2 O-0.63%, TiO 2 -0.25%, the main components after normalization are: SiO 2 -11.98%, Al 2 O 3 -8.78%, CaO-64.09%, MgO-7.60%, Fe 2 O 3 -3.17%, FeO-1.95%, Na 2 O-1.12%, K 2 O-0.94%, TiO 2 -0.37%.

[0045] Step 2: Determine (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio:

[0046] (SiO 2 +Al 2 O 3 ) / (CaO+MgO)=0.29<1.1, add 22wt.% quartz sand and 30wt.% kaolinite to the dechlorinated fly ash, adjust (SiO 2 +Al 2 O 3) / (CaO+MgO) ratio = 1.26, between 1.1-2.2; the adjusted mixture composition is: SiO 2 -37.78%, Al 2 O 3 -15.55%, CaO-37.74%, MgO-4.48%, Fe 2 O 3 -0.45%, FeO-2.56%, Na 2 O-0.66%, K 2 O-0.55%, TiO 2 -0.22%.

[0047] Step 3: Determine Al 2 O 3 / MgO ratio:

[0048] Al 2 O 3 / MgO ratio = 3.47>2.2, readjust the proportion of additives, add 30wt.% quartz sand, 24.5wt.% kaolinite and 5wt.% magnesite to the dechlorinated fly ash, and after adjustment (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.26, between 1.1-2.2; Al 2 O 3 / MgO ratio = 2.08, between 1.5-2.2. The adjusted mixture composition is: SiO 2 -40.38%, Al 2 O 3 -13.04%, CaO-36.05%, MgO-6.28%, Fe 2 O 3 -0.43%, FeO-2.45%, Na 2 O-0.63%, K 2 O-0.53%, TiO 2 -0.21%.

[0049] Step 4: Due to (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.26 < 1.5, so there is no need to adjust the Fe content in the material. 2 O 3 +Mass fraction of FeO.

[0050] Step 5: Classification, conversion and combination of oxides in the mixture:

[0051] SiO2 * =40.38%

[0052] Al 2 O 3 * =13.04%+102 / 160×0.43%+102 / 79.8×0.21%=13.60%

[0053] CaO * =36.05%+56 / 40×6.28%+56 / 46×0.63%+56 / 94×0.53%+56 / 72×2.45%=47.63%

[0055] SiO 2 * 、Al 2 O 3 * 、CaO * After normalization, SiO 2 * =39.75%, Al 2 O 3 * =13.38%, CaO * =46.87%.

[0056] Step 5: Determine (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO 2 * / Al 2 O 3 * Ratio of:

[0057] (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO 2 * / Al 2 O 3 * The ratio = 2.97 is between 2-7; all ratios meet the adjustment requirements.

[0058] Step 6: After adjustment, the viscosity of the mixture at 1400°C is η=0.73 Pa·s, the melting point is T=1350°C, and the fiber-forming temperature range corresponding to the viscosity of 1-3 Pa·s is 134°C.

[0059] Example 2

[0060] The material control method for preparing rock wool and slag wool using dechlorinated fly ash from Plant B includes the following steps:

[0061] Step 1: Analyze the components of dechlorinated fly ash using X-ray fluorescence analysis and chemical titration:

[0062] The mass percentage of the main components of dechlorinated fly ash is: SiO 2 -10.69%, Al 2 O 3 -3.93%, CaO-62.61%, MgO-3.14%, Fe 2 O 3 -1.77%, FeO-0.98%, Na 2 O-0.68%, K 2 O-0.75%, TiO 2 -0.19%, the main components after normalization are: SiO 2 -12.62%, Al 2 O 3 -4.64%, CaO-73.88%, MgO-3.71%, Fe 2 O 3 -2.09%, FeO-1.16%, Na 2 O-0.8%, K 2 O-0.89%, TiO 2 -0.22%.

[0063] Step 2: Determine (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio:

[0064] (SiO 2 +Al 2 O 3 ) / (CaO+MgO)=0.22<1.1, add 80% quartz sand to the dechlorinated fly ash, adjust (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.4, the main components of the adjusted mixture are: SiO 2 -54.16%, Al 2 O 3-2.43%, CaO-38.76%, MgO-1.94%, Fe 2 O 3 -1.10%, FeO-0.61%, Na 2 O-0.42%, K 2 O-0.46%, TiO 2 -0.12%.

[0065] Step 3: Determine Al 2 O 3 / MgO ratio:

[0066] Al 2 O 3 / MgO ratio = 1.3 < 1.5, the proportion of additives needs to be readjusted, 70% quartz sand, 15% kaolinite and 4% magnesite are added to the dechlorinated fly ash, and the (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.4, between 1.1-2.2; Al 2 O 3 / MgO ratio = 2.0, between 1.5-2.2. The adjusted mixture composition is: SiO 2 -53.57%, Al 2 O 3 -5.59%, CaO-35.5%, MgO-2.86%, Fe 2 O 3 -0.23%, FeO-1.33%, Na 2 O-0.39%, K 2 O-0.43%, TiO 2 -0.11%.

[0067] Step 4: Due to (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.4 < 1.5, so there is no need to adjust the Fe content in the material. 2 O 3 +Mass fraction of FeO.

[0068] Step 5: Classification, conversion and combination of oxides in the mixture:

[0069] SiO 2 * =53.57%

[0070] Al 2 O 3 *=5.59%+102 / 160×0.23%+102 / 79.8×0.11%=5.88%

[0071] CaO * =35.5%+56 / 40×2.86%+56 / 62×0.39%+56 / 94×0.43%+56 / 72×1.33%=46.6%

[0072] SiO 2 * 、Al 2 O 3 * 、CaO * After normalization, SiO 2 * =53.25%,Al 2 O 3 * =5.85%, CaO * =40.9%.

[0073] Step 6: Determine (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO 2 * / Al 2 O 3 * Ratio of:

[0074] (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO = 1.44, between 1-1.7; 2 * / Al 2 O 3 * The ratio = 9.1>7, which does not meet the requirements.

[0075] It is necessary to return to step 2 to readjust the additive composition and ratio. Add 58% quartz sand, 35% kaolinite and 12% magnesite to the dechlorinated fly ash to adjust (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.4, between 1.1-2.2; Al 2 O 3 / MgO ratio = 2.0, between 1.5-2.2. The adjusted mixture composition is: SiO 2 -46.89%, Al 2 O 3 -10.07%, CaO-35.52%, MgO-5.04%, Fe 2 O 3 -0.23%, FeO-1.33%, Na 2 O-0.39%, K 2 O-0.43%, TiO 2 -0.11%.

[0076] Classification, conversion and combination of oxides in the mixture:

[0077] SiO 2 * =46.89%

[0078] Al 2 O 3 * =10.07%+102 / 160×0.23%+102 / 79.8×0.11%=10.37%

[0079] CaO * =35.52%+56 / 40×5.04%+56 / 62×0.39%+56 / 94×0.43%+56 / 72×1.33%=44.21%

[0081] SiO 2 * 、Al 2 O 3 * 、CaO * After normalization, SiO 2 * =46.21%, Al 2 O 3 * =10.22%, CaO * =43.57%.

[0082] (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO = 1.3, between 1-1.7; 2 * / Al 2 O 3* The ratio = 4.52, between 2-7; all ratios meet the adjustment requirements.

[0083] Step 7: After adjustment, the viscosity of the mixture at 1400°C is η=1.13 Pa·s, the melting point is T=1334°C, and the fiber-forming temperature range corresponding to the viscosity of 1-3 Pa·s is 130°C.

[0084] Example 3

[0085] The material control method for preparing rock wool and slag wool using dechlorinated fly ash from Plant C includes the following steps:

[0086] Step 1: Analyze the components of dechlorinated fly ash using X-ray fluorescence analysis and chemical titration:

[0087] The mass percentage of the main components of dechlorinated fly ash is: SiO 2 -32.36%, Al 2 O 3 -9.05%, CaO-20.96%, MgO-1.52%, Fe 2 O 3 -3.38%, FeO-0.32%, Na 2 O-0.86%, K 2 O-0.42%, TiO 2 -0.31%, the main components after normalization are: SiO 2 -46.78%, Al 2 O 3 -13.08%, CaO-30.3%, MgO-2.2%, Fe 2 O 3 -4.89%, FeO-0.46%, Na 2 O-1.24%, K 2 O-0.61%, TiO 2 -0.45%.

[0088] Step 2: Determine (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio:

[0089] (SiO 2 +Al 2 O 3 ) / (CaO+MgO)=1.84, between 1.1-2.2, no adjustment is required.

[0090] Step 3: Determine Al 2 O 3 / MgO ratio:

[0091] Al 2 O 3 / MgO ratio = 5.95>2.2, it is necessary to readjust the proportion of additives, add 12% iron tailings and 10% magnesite to the dechlorinated fly ash, and adjust (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.84, between 1.1-2.2; Al 2 O 3 / MgO ratio = 1.59, between 1.5-2.2. The main components of the adjusted mixture are: SiO 2 -47.13%, Al 2 O 3 -12.29%, CaO-24.69%, MgO-7.73%, Fe 2 O 3 -0.79%, FeO-4.46%, Na 2 O-1.36%, K 2 O-1.13%, TiO 2 -0.41%.

[0092] Step 4: Due to (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.84>1.5, it is necessary to adjust the Fe content in the material 2 O 3 +FeO mass fraction:

[0093] Fe in the mixture 2 O 3 +FeO mass fraction = 5.25% > 4%, no need to adjust Fe 2 O 3 +Mass fraction of FeO.

[0094] Step 5: Classification, conversion and combination of oxides in the mixture:

[0095] SiO 2 * =47.13%

[0096] Al 2 O 3 * =12.29%+102 / 160×0.79%+102 / 79.8×0.41%=13.35%

[0097] CaO *=24.69%+56 / 40×7.73%+56 / 62×1.36%+56 / 94×1.13%+56 / 72×4.46%=40.89%

[0099] SiO 2 * 、Al 2 O 3 * 、CaO * After normalization, SiO 2 * =46.50%,Al 2 O 3 * =13.17%, CaO * =40.34%.

[0100] Step 6: Determine (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO 2 * / Al 2 O 3 * Ratio of:

[0101] (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO = 1.48, between 1-1.7; 2 * / Al 2 O 3 * The ratio = 3.53, between 2-7; all ratios meet the adjustment requirements.

[0102] Step 7: After adjustment, the viscosity of the mixture at 1400°C is η=1.73 Pa·s, the melting point is T=1366°C, and the fiber-forming temperature range corresponding to the viscosity of 1-3 Pa·s is 125°C.

[0103] Example 4

[0104] The material control method for preparing rock wool and slag wool using dechlorinated fly ash from Plant D comprises the following steps:

[0105] Step 1: Analyze the components of dechlorinated fly ash using X-ray fluorescence analysis and chemical titration:

[0106] The mass percentage of the main components of dechlorinated fly ash is: SiO 2 -49.82%, Al 2 O 3 -11.20%, CaO-14.93%, MgO-6.33%, Fe 2 O 3 -1.92%, FeO-1.03%, Na 2 O-0.56%, K 2 O-0.48%, TiO 2 -0.23%, the contents of the main components after normalization are: SiO 2 -57.60%、Al 2 O 3 -12.95%, CaO-17.26%, MgO-7.32%, Fe 2 O 3 -2.22%, FeO-1.19%, Na 2 O-0.65%, K 2 O-0.55%, TiO 2 -0.27%.

[0107] Step 2: Determine (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio:

[0108] (SiO 2 +Al 2 O 3 ) / (CaO+MgO)=2.87>2.2, 12.8% dolomite is added to the dechlorinated fly ash to adjust (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 2.2, between 1.1-2.2. The main components of the adjusted mixture are: SiO 2 -53.46%, Al 2 O 3 -12.02%, CaO-20.2%, MgO-9.8%, Fe 2 O 3 -0.47%, FeO-2.69%, Na 2 O-0.60%, K 2 O-0.52%, TiO 2 -0.25%.

[0109] Step 3: Determine Al 2 O 3 / MgO ratio:

[0110] Al 2 O 3 / MgO ratio = 1.24 < 1.5, the proportion of additives needs to be readjusted, 13% limestone, 7% dolomite, and 12% kaolinite are added to the dechlorinated fly ash, and the (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 2.2, between 1.1-2.2; Al 2 O 3 / MgO ratio = 2.03, between 1.5-2.2. The main components of the adjusted mixture are: SiO 2 -51.41%, Al 2 O 3 -14.79%, CaO-22.59%, MgO-7.3%, Fe 2 O 3 -0.41%, FeO-2.33%, Na 2 O-0.52%, K 2 O-0.45%, TiO 2 -0.21%.

[0111] Step 4: Due to (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 2.2>1.5, it is necessary to adjust the Fe content in the material 2 O 3 +FeO mass fraction:

[0112] Fe 2 O 3 +FeO mass fraction = 3.08% < 4%, add 5% iron oxide scale to the dechlorinated fly ash to adjust Fe 2 O 3 +FeO mass fraction = 7.91%, between 4% and 10%. The main components of the adjusted mixture are: SiO 2 -49.13%, Al 2 O 3 -14.14%, CaO-21.58%, MgO-6.97%, Fe 2 O 3 -1.06%, FeO-5.99%, Na 2 O-0.5%, K 2 O-0.43%, TiO 2 -0.2%.

[0113] Step 5: Classification, conversion and combination of oxides in the mixture:

[0114] SiO 2 * =49.13%

[0115] Al 2 O 3 * =14.14%+102 / 160×1.06%+102 / 79.8×0.2%=15.11%

[0116] CaO * =21.58%+56 / 40×6.97%+56 / 62×0.5%+56 / 94×0.43%+56 / 72×5.99%=36.71%

[0118] SiO 2 * 、Al 2 O 3 * 、CaO * After normalization, SiO 2 * =48.67%, Al 2 O 3 * =14.97%, CaO * =36.36%.

[0119] Step 6: Determine (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO 2 * / Al 2 O 3 * Ratio of:

[0120] (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of =1.75>1.7, SiO 2 * / Al 2 O 3 * The ratio = 3.25 is between 2-7, and the ratio does not meet the requirements.

[0121] It is necessary to return to step 2 to readjust the additive composition and ratio. Add 8% limestone, 6.5% dolomite and 2% kaolinite to the dechlorinated fly ash to adjust (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 2.2, between 1.1-2.2; Al 2 O 3 / MgO ratio = 1.55, between 1.5-2.2. The main components of the adjusted mixture are: SiO 2 -50.2%, Al 2 O 3 -11.86%, CaO-21.15%, MgO-7.67%, Fe 2 O 3 -1.18%, FeO-6.68%, Na 2 O-0.55%, K 2 O-0.47%, TiO 2 -0.23%.

[0122] Classification, conversion and combination of oxides in the mixture:

[0123] SiO 2 * =50.2%

[0124] Al 2 O 3 * =11.86%+102 / 160×1.18%+102 / 79.8×0.23%=12.95%

[0125] CaO * =21.15%+56 / 40×7.67%+56 / 62×0.55%+56 / 94×0.47%+56 / 72×6.68%=37.87%

[0127] SiO 2 * 、Al 2 O 3 * 、CaO * After normalization, SiO 2 * =49.69%, Al 2 O 3 * =12.82%, CaO * =37.49%.

[0128] (SiO2 * +Al 2 O 3 * ) / CaO * The ratio of SiO = 1.67, between 1-1.7; 2 * / Al 2 O 3 * The ratio = 3.88, between 2-7; all ratios meet the adjustment requirements.

[0129] Step 7: After adjustment, the viscosity of the mixture at 1400°C is η=2.55 Pa·s, the melting point is T=1425°C, and the fiber-forming temperature range corresponding to the viscosity of 1-3 Pa·s is 129°C.

[0130] Example 5

[0131] The material control method for preparing rock wool and slag wool using dechlorinated fly ash from Plant E includes the following steps:

[0132] Step 1: Analyze the components of dechlorinated fly ash using X-ray fluorescence analysis and chemical titration:

[0133] The mass percentage of the main components of dechlorinated fly ash is: SiO 2 -16.72%, Al 2 O 3 -4.23%, CaO-32.68%, MgO-1.62%, Fe 2 O 3 -2.16%, FeO-0.23%, Na 2 O-0.69%, K 2 O-0.57%, TiO 2 -0.42%, the main components after normalization are: SiO 2 -28.19%, Al 2 O 3 -7.13%, CaO-55.09%, MgO-2.73%, Fe 2 O 3 -3.64%, FeO-0.39%, Na 2 O-1.16%, K 2 O-0.96%, TiO 2 -0.71%.

[0134] Step 2: Determine (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio:

[0135] (SiO 2 +Al 2 O 3 ) / (CaO+MgO)=0.61<1.1, add 47% iron tailings to dechlorinated fly ash, adjust (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.6, between 1.1-2.2; the main components of the adjusted mixture are: SiO 2 -45.77%, Al 2 O 3 -9.54%, CaO-31.77%, MgO-2.77%, Fe 2 O 3 -0.78%, FeO-4.45%, Na 2 O-1.78%, K 2 O-2.58%, TiO 2 -0.56%.

[0136] Step 3: Determine Al 2 O 3 / MgO ratio:

[0137] Al 2 O 3 / MgO ratio = 3.45>2.2, the proportion of additives needs to be readjusted, 47% iron tailings, 6% kaolinite and 7% magnesite are added to the dechlorinated fly ash, and the (SiO 2 +Al 2 O 3 ) / (CaO+MgO) ratio = 1.6, between 1.1-2.2; Al 2 O 3 / MgO ratio = 1.98, between 1.5-2.2. The main components of the adjusted mixture are: SiO 2 -44.8%, Al 2 O 3 -10.9%, CaO-29.4%, MgO-5.49%, Fe 2 O 3 -0.73%, FeO-4.12%, Na 2 O-1.65%, K 2 O-2.39%, TiO 2 -0.52%.

[0138] Step 4: Due to (SiO 2 +Al 2 O 3) / (CaO+MgO) ratio = 1.84>1.5, it is necessary to adjust the Fe content in the material 2 O 3 +FeO mass fraction:

[0139] Fe in the mixture 2 O 3 +FeO mass fraction = 4.84% > 4%, no need to adjust Fe 2 O 3 +Mass fraction of FeO.

[0140] Step 5: Classification, conversion and combination of oxides in the mixture:

[0141] SiO 2 * =44.8%

[0142] Al 2 O 3 * =10.9%+102 / 160×0.0.73%+102 / 79.8×0.52%=12.05%

[0143] CaO * =29.4%+56 / 40×5.49%+56 / 62×1.65%+56 / 94×2.39%+56 / 72×4.12%=43.21%

[0145] SiO 2 * 、Al 2 O 3 * 、CaO * After normalization, SiO 2 * =44.77%, Al 2 O 3 * =12.04%, CaO * =43.19%.

[0146] Step 6: Determine (SiO 2 * +Al 2 O 3 * ) / CaO * The ratio of SiO 2 * / Al 2 O 3 * Ratio of:

[0147] (SiO2 * +Al 2 O 3 * ) / CaO * The ratio of SiO = 1.32, between 1-1.7; 2 * / Al 2 O 3 * The ratio = 3.72, between 2-7; all ratios meet the adjustment requirements.

[0148] Step 7: After adjustment, the viscosity of the mixture at 1400°C is η=1.19 Pa·s, the melting temperature is T=1335°C, and the fiber-forming temperature range corresponding to the viscosity of 1-3 Pa·s is 132°C.

[0149] According to the detection method in Appendix C of the relevant national standards "GB / T 25975-2018 Rockwool products for external thermal insulation of building exterior walls", "GB / T5480-2017 Test methods for mineral wool and its products" and "GB / T 18046-2017 Granulated blast furnace slag powder for cement, mortar and concrete", the average diameter, slag ball content and vitreous content of the fibers prepared by the materials adjusted in the above embodiment were tested and analyzed, and the results are shown in Table 1 below:

[0150] Table 1 Performance evaluation results of fibers prepared from materials of Examples 1-5

[0151] Example Average fiber diameter / μm Slag ball content / % Vitreous content / % 1 4.3 4.4 96.15 2 4.5 4.8 98.94 3 5.1 4.5 99.74 4 5.6 6.7 99.91 5 4.8 4.7 99.89

[0152] According to the material control method of the present invention, the average diameter and slag ball content of mineral wool fibers prepared from dechlorinated fly ash meet the limit values ​​in the national standards; the average fiber diameter is less than 6 μm, the slag ball content is less than 7%, and the fiber glass content is greater than the 85% limit value in "GB / T41015-2021 Technical Requirements for Solid Waste Vitrification Products".

[0153] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash, characterized in that: The following steps are involved: S1. Analyze the composition of dechlorinated fly ash by X-ray fluorescence analysis to obtain the mass percentage of SiO2, Al2O3, CaO, MgO, Fe2O3, FeO, Na2O, K2O and TiO2 in the dechlorinated fly ash, and perform normalization; S2. Adjust the ratio of (SiO2+Al2O3) / (CaO+MgO) in the dechlorinated fly ash so that the ratio of (SiO2+Al2O3) / (CaO+MgO) is 1.1-2.2; adjust the ratio of Al2O3 / MgO in the dechlorinated fly ash so that the ratio of Al2O3 / MgO is 1.5-2.2 to obtain a mixed material; S3. The oxides in the adjusted mixture are classified according to their effects on the physical properties of the slag and the performance of the mineral wool fibers, and are divided into the formation, intermediates and altered forms of the mineral wool glass fiber network with similar properties to SiO2, Al2O3 and CaO, and are converted according to the corresponding conversion coefficients and incorporated into the corresponding SiO2, Al2O3 and CaO components. The conversion method is as follows: SiO2 * =SiO2 <h2 style=";text-align:left;direction:ltr">Al2O3<h2 style=";text-align:left;direction:ltr"> * <h2 style=";text-align:left;direction:ltr"> (Al2O3+102 / 160·Fe2O3+102 / 79.8·TiO2) High * =CaO+56 / 40·MgO+56 / 46·Na2O+56 / 94·K2O+56 / 72·FeO The obtained SiO2 * 、Al2O3 * 、CaO * Perform normalization processing; S4. Determine the rationality of the materials for the adjusted dechlorinated fly ash insulation cotton, ensure that the ratio of (SiO2*+Al2O3*) / CaO* is 1-1.7, and the ratio of SiO2* / Al2O3* is 2-7. If the conditions are not met, readjust the dechlorinated fly ash components until the conditions are met; S5. After adjusting the mass proportion of the main components in the dechlorinated fly ash, the composition of the dechlorinated fly ash meets the material requirements for preparing thermal insulation cotton, and the key properties of the high-temperature melt after melting meet the following requirements: the viscosity of the slag at 1400°C is less than 3Pa·s, and the melting temperature of the slag is less than 1450°C.

2. The material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash according to claim 1, characterized in that: The method for adjusting the mass percentage of the dechlorinated fly ash component in step S2 is: If the ratio of (SiO2+Al2O3) / (CaO+MgO) is less than 1.1, then ore or solid waste additives rich in SiO2 and Al2O3 are added to the dechlorinated fly ash; If the ratio of (SiO2+Al2O3) / (CaO+MgO) is greater than 2.2, then ore or solid waste additives rich in CaO and MgO are added to the dechlorinated fly ash; If the ratio of 1.1≤(SiO2+Al2O3) / (CaO+MgO)≤2.2, and the ratio of Al2O3 / MgO<1.5, kaolinite is added to the dechlorinated fly ash to adjust the mass fraction of Al2O3; If the ratio of 1.1≤(SiO2+Al2O3) / (CaO+MgO)≤2.2, and the ratio of Al2O3 / MgO>2.2, then add magnesite to the dechlorinated fly ash to adjust the MgO mass fraction; If 1.1≤(SiO2+Al2O3) / (CaO+MgO) ratio≤2.2, and 1.5≤Al2O3 / MgO ratio≤2.2, the first stage adjustment is completed.

3. The material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash according to claim 2, characterized in that: The ore or solid waste additive rich in SiO2 and Al2O3 is one or more of quartz sand, kaolinite, fly ash, and iron tailings; the ore or solid waste additive rich in CaO and MgO is one or more of limestone, dolomite, magnesite, blast furnace slag, and steel slag.

4. The material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash according to claim 2, characterized in that: In the component adjustment, when the ratio of (SiO2+Al2O3) / (CaO+MgO) is ≥1.5, the mass fraction of Fe2O3+FeO in the dechlorinated fly ash is adjusted to >4%. The adjustment method is: When the ratio of (SiO2+Al2O3) / (CaO+MgO) is ≥1.5, and the mass fraction of Fe2O3+FeO is <4%, an ore or solid waste additive rich in Fe2O3 and FeO is added to the dechlorinated fly ash; When the ratio of (SiO2+Al2O3) / (CaO+MgO) is 1.1≤1.5 or the ratio of (SiO2+Al2O3) / (CaO+MgO) is 1.5<2.2 and the mass fraction of Fe2O3+FeO is ≥4%, the second stage adjustment is completed.

5. The material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash according to claim 4, characterized in that: The ore or solid waste additive rich in Fe2O3 and FeO is one or more of hematite, Bayer red mud, and iron oxide scale.

6. The material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash according to claim 1, characterized in that: The specific method for readjusting the dechlorinated fly ash components in step S4 is: If (SiO2 * +Al2O3 * ) / CaO * The ratio is less than 1, and the amount of ore or solid waste additives containing SiO2 and Al2O3 needs to be appropriately increased; If (SiO2 * +Al2O3 * ) / CaO * The ratio is greater than 1.7, and the amount of ore or solid waste additives containing CaO and MgO needs to be appropriately increased; If 1≤(SiO2 * +Al2O3 * ) / CaO * The ratio is ≤1.7, and SiO2 * / Al2O3 * If the ratio is less than 2 or greater than 7, it is necessary to adjust the proportion of ore or solid waste additives containing SiO2 and Al2O3 to adjust the ratio of SiO2 and Al2O3; If 1≤(SiO2 * +Al2O3 * ) / CaO * The ratio is ≤1.7, and 2≤SiO2 * / Al2O3 * If the ratio is ≤7, the adjustment is completed.

7. The material control method for preparing rock wool and slag wool from dechlorinated waste incineration fly ash according to claim 1, characterized in that: The calculation formula for the viscosity η at 1400° C. in step S5 is: The calculation formula of the melting temperature of slag is: T=-742.705X 3 +3683.7511X 2 -5753.5189X+4219.9091 Where X=(SiO2 * +Al2O3 * ) / CaO * The fiber-forming temperature range corresponding to the slag viscosity of 1-3 Pa·s is greater than 100°C.